The Effects of Organizational Culture, Leadership Style and Job Satisfaction Towards Organizational Commitment - Yehya, Suhaeb S. (2010)
The Iraqi telecommunications is fast growing industry in Iraq and there is a lot of potential and opportunities in this area from investment perspective. Due to war which has destroyed the infrastructure of telecommunication and there is a high need for companies and investors to participate in this repairing (Izdihar, 2006). Due to uncertainty in the region the telecommunication companies are providing limited salary and limited incentives to their employees and on the other hand these employees are influenced by companies' inappropriate leadership style. Secondly the employees of these companies are not satisfied, with the culture, as organizational culture is one of the important factor that can influence organizational commitment and accordingly the employees are committed to the organization. Due to all the above reason these employee are not committed to their job. Iraq is experiencing a boom in term of technological investment, especially in the mobile telecommunication industry. The Iraqi companies need strategic leaders who can create organization culture to influence job satisfaction and in the end of the day these employees can be more committed to their jobs. Culture plays very important role in influencing organizational commitment. Base on past recommendation it has been identified to investigate the factors of leadership style, job satisfaction, and culture as independent variables influencing organizational commitment as dependent variable. Base on the future recommendation by (Lahiry, 1994), that there is a need to examine the organizational commitment in more vital perspective and needed to find more avenues. This study is unique as there are very little organizational behavior Iraqi research has been conducted on Iraqi telecommunication industry. This study will add value by providing a significant contribution towards organizational commitment in Iraq.